Cathode intramolecular electron transfer of the Braga-Goodenough Li-S rechargeable battery - Masanori Sakai (Journal of Electrochemical Science and Engineering)
Braga-Goodenough all-solid-state Li-S discharges beyond the theoretical capacity of the S8 cathode and deposits Li during discharge, and the paradigm-shifting phenomena have been analysed by the previous mechanism. The mechanism has explained the phenomena coherently, except for an intrinsic question raised for the Li deposition step. This paper reviews and revises the previous mechanism and presents a new mechanism involving intramolecular tunnelling electron transfer within an adsorbate to clarify and resolve the issue. The formation of the adsorbate S8-Li+(sf)(ad) (sf-surface states) is essential and characteristic, being the common step for both mechanisms. Since this adsorbate electron energy level is around the S8- or S8 cathode potential range, the previous mechanism showed that electrons from the Li anode reduced Li+(sf)(ad) in the S8-Li+(sf)(ad) to deposit Li. However, this electron flow followed the established concept of battery discharge and raised the question of why the reduction path was not through S8-, but only through Li+(sf)(ad) in the adsorbate. The present new mechanism answers this question through the tunnelling electron transfer from S8- to Li+(sf)(ad) within the adsorbate, which is entirely congruent with the heterojunction physics analysis, and demonstrates a new overall reaction equation. Maximum Li deposition cycles and discharge capacity are also discussed.